PERTIMBANGAN HAKIM DALAM MENJATUHKAN PUTUSAN TERHADAP WANPRESTASI PERJANJIAN KREDIT ANTARA PT. BANK MANDIRI (PERSERO) TBK DENGAN DEBITUR (STUDI PUTUSAN NOMOR 34/PDT.G.S/2020/PN.PDG) - Tuti Kelana Sembiring (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
People in developed and developing countries, especially in Indonesia, really need banks to carry out financial activities in carrying out their daily activities. One of the bank products apart from collecting funds from the public is lending, as regulated in Article 1 paragraph (11) of Law of the Republic of Indonesia Number 10 of 1998 concerning amendments to Law Number 7 of 1992 concerning Banking. The breach of promise (default) in decision Number 34/Pdt.G.S/2020/PN.Pdg is in the form of a delay in returning the agreed credit. The problem in this thesis is first, what is the judge's consideration in making a decision regarding the credit agreement default between PT. Bank Mandiri (Persero) Tbk with the debtor in decision Number 34/Pdt.G.S/2020/PN.Pdg? Second, what are the legal consequences arising from the Judge's considerations in Decision Number 34/Pdt.G.S/2020/PN.Pdg regarding the credit agreement default between PT. Bank Mandiri (Persero) Tbk with debtors? The approach used in this research is a normative juridical approach, namely by listing the laws and regulations related to the issue discussed, namely decision Number 34/Pdt.G.S/2020/PN.Pdg. The data used is secondary data, which includes primary legal materials, secondary legal materials and tertiary legal materials collected through literature study, data management and analysis, then the data is edited first and presented in the form of descriptive analysis of the results. Based on research and discussion, it can be concluded that: first, the judge's consideration in making a decision regarding the credit agreement default between PT. Bank Mandiri (Persero) Tbk with the debtor in decision Number 34/Pdt.G.S/2020/PN.Pdg is based on the facts revealed at trial and connected with evidence from letters that correspond to each other and summons served three times. by the plaintiff against the defendant. Second, the legal consequences of the Judge's considerations in Decision Number 34/Pdt.G.S/2020/PN.Pdg are; 1. Grant the Plaintiff's lawsuit in part; 2. Declare that the Defendant has committed an act of Default; 3. Sentence the Defendant to pay in full all arrears; 4. Sentence the Defendant to pay compensation in the form of interest to the Plaintiff of 6% (six percent); 5. Sentence the Defendant to pay the court costs incurred in the case.Keywords: Default, Judge's Consideration, Decision